SISTEM KONTROL PENCATUAN DAYA PADA BEBAN LISTRIK ARUS BOLAK-BALIK ANTARA SISTEM SOLAR CELL DAN JARING PLN SATU FASA - Ahmad Syamsul; Akhmad Musafa (MAESTRO, 2019)
The Final Project, a system of alternating electric current power is designed between a solar cell system and a single phase PLN net. The system designed consists of 2 units of 50 wp solar cell capacity that are connected parallel, 1 unit buck boost converter, 1 unit 300 watt inverter, 1 unit Arduino MEGA 2560 controller board, 3 voltage sensor units, 2 current sensor units, 1 relay unit 4 channels, 1 unit up to an adapter card, 1 unit charge controller and 1 unit battery. The working method of this system is that the solarcell circuit generates voltage and current connected to the DC-DC converter input will be detected by a voltage sensor and current sensor, as analog signal input to the Arduino Mega 2560 controller board. Where is the P&O MPPT algorithm on the Arduino Mega 2560 controller board will produce an output signal in the form of a PWM duty cycle to control the output of the DC-DC converter. The DC-DC converter output connected to the inverter to be converted into AC voltage, will be re-detected by the voltage sensor and current sensor as analog signal input to the Arduino Mega 2560 controller board. Where the switching algorithm in the Arduino Mega 2560 controller board will produce HIGH or LOW as input from relay circuit. The relay circuit will switch the voltage and current from the DC-DC converter or battery to the inverter or from the pln source 220 volts to the load. The output power in the DC-DC converter with an average efficiency of 44.20%. The solar cell system that uses a source of 2 50wp solar cell units is arranged in parallel with a 12 volt 50Ah backup battery with a 96 watt load from 4 24 watt lamp units can supply a load for 40 minutes in 1 hour with the average output power of the solar cell at 9.48 watts.